Hypermedia APIs and their use for enhancing integration of IT services - Annau, Mike; Šebesta, Michal; Jelínek, Ivan; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2016)
This paper's aim is to design and implement a tool transforming REST Web APIs into APIs which facilitate the integration process. The improvement of integration is mainly divided into two parts: The embedding of semantic data in order to establish a common understanding of objects, properties and relations and the possibility to navigate through the API structure in an easy and automated way. The theoretical part is dealing with the fundamentals of Web APIs, today's related trends and the API's shortages and points of improvement. Another objective of this paper is to compare current data standards of output formats for so called Hypermedia APIs, whereas the most suitable components will be chosen as the output format of this paper's resulting tool. The practical part is dealing with the design and implementation of the tool being developed. Included, there is the description of test scenarios, related benefits for the tool's users as well as a final evaluation of the resulting tool and a discussion of the tool's future potential. The benefits of the tool are evaluated in a case study.
Vedoucí práce: Michal Šebesta
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: informační systémy a technologie [obor dipl. práce]; diplomové práce; master's theses